If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + -21 = 25 + -3x Reorder the terms: -21 + x = 25 + -3x Solving -21 + x = 25 + -3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. -21 + x + 3x = 25 + -3x + 3x Combine like terms: x + 3x = 4x -21 + 4x = 25 + -3x + 3x Combine like terms: -3x + 3x = 0 -21 + 4x = 25 + 0 -21 + 4x = 25 Add '21' to each side of the equation. -21 + 21 + 4x = 25 + 21 Combine like terms: -21 + 21 = 0 0 + 4x = 25 + 21 4x = 25 + 21 Combine like terms: 25 + 21 = 46 4x = 46 Divide each side by '4'. x = 11.5 Simplifying x = 11.5
| 4x+40=(4x+40)*2 | | -2x-6-3=1 | | 2(6d+3)=18-3(16d-3d) | | -104=-6x-3x+4 | | 10a+5[a-3]=15 | | 3-x+3=5x | | 6-8x=7x-10+11 | | 14-3a+7a=94 | | 4q+4=-2q-8 | | -6(x-1)=14-2x | | 9x-27=9(11-x) | | 6-2x=-12 | | -2x+4(3x+5)=-60 | | 0.3x-0.4=2 | | 7p-5=69+8 | | 5(x+2)=(x+6) | | -8k+k=-14 | | x/4-x/3= | | .5x+5=17 | | 2(x+1)+4=16 | | 5-3(x-7)=26-2x | | 15+2x-3=2x+5 | | 5(4x+9)=9(2x+3) | | 0.5(14x+8)=6x+8 | | -4m-11=-3m-14 | | 6x+9x-21=105-6x | | -2k-5=-k+3 | | m-9m-8m-5= | | 1+x=x-5 | | 2x+6x+8=36 | | -3(m-8)=3 | | P=22p |